2008
DOI: 10.1002/pola.23016
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated clay particles in polystyrene by RAFT mediated miniemulsion polymerization

Abstract: RAFT grafted montmorillonite (MMT) clays [i.e., N,N-dimethyl-N-(4-(((phenylcarbonothioyl)thio)methyl)benzyl)ethanammonium-MMT (PCDBAB-MMT) and N-(4-((((dodecylthio)carbonothioyl)thio)methyl)benzyl)-N,N-dimethylethanammonium-MMT (DCTBAB-MMT)] of various loadings were dispersed in styrene (S) monomer and the resultant mixtures emulsified and sonicated in the presence of a hydrophobe (hexadecane) into miniemulsions. The stable miniemulsions thus obtained were polymerized to yield encapsulated polystyrene-clay nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 95 publications
(129 reference statements)
10
45
1
Order By: Relevance
“…Other substrates to which the 'grafting-from' approach has been applied include silicon wafers, [179,213,524] poly(silsesquioxane), [210,228] [105] 408 [142] (POSS), [350,360,361] indium-tin oxide (ITO) surfaces, [176] carbon nanotubes, [525] titania particles, [526,527] clay, [528][529][530] cadmium sulfide nanoparticles, [531] cellulose, [532][533][534][535] and PVDF membranes. [536] …”
Section: Grafting-from Processesmentioning
confidence: 99%
“…Other substrates to which the 'grafting-from' approach has been applied include silicon wafers, [179,213,524] poly(silsesquioxane), [210,228] [105] 408 [142] (POSS), [350,360,361] indium-tin oxide (ITO) surfaces, [176] carbon nanotubes, [525] titania particles, [526,527] clay, [528][529][530] cadmium sulfide nanoparticles, [531] cellulose, [532][533][534][535] and PVDF membranes. [536] …”
Section: Grafting-from Processesmentioning
confidence: 99%
“…Therefore, decreasing radical concentration can directly affect the polymerization rate and monomer conversion. 30 These unreacted functionalities as impurities can increase chain transfer and termination of propagating radicals and disturb the equilibrium of ATRP reaction, which leads to higher polydispersity values.…”
Section: Kinetics Of Srandni Atrp Of Styrene Using a Dual Initiator Systemmentioning
confidence: 99%
“…Later, Zhang et al [25] used the in situ RAFT polymerization with an intercalated RAFT agent to produce polystyrene/MMT nanocomposites with exfoliated structure and higher thermal stability compared to pure polystyrene. Hartmann et al [45,46] have also shown the effectiveness of intercalated RAFT agents on the control of polymerization in bulk and miniemulsion during PCNs synthesis. The effect of clay loadings for the preparation of nanocomposites has been reported by Ding et al [26] who found exfoliated or intercalated structures, based on the different clay loadings.…”
Section: Polymer/clay Nanocomposites By Atrpmentioning
confidence: 99%